Pengaruh Persepsi Kualitas Dan Persepsi Resiko Terhadap Keputusan Pembelian Susu Formula - Rahayu Mardikaningsih (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2019)
Before determining the purchase decision of Isomil Plus Advanced Soya formula milk, consumers will evaluate the quality and risk of the dairy product, especially for children who have allergies to cow's milk protein, if perceived by consumers to be of high quality, they will decided to buy it, on the contrary if the perception of the risk of consuming milk is higher than the quality, they will cancel their intention to buy it. The sampling technique in this study is the accidential sampling method. The population in this study involved 100 respondents who used Isomil Plus Advanced Soya formula milk in Surabaya City. The results showed that the perception of quality had a significant positive effect on the purchasing decisions of Isomil Plus Advanced Soya formula milk in Surabaya City. The results showed that the perception of risk had a significant positive effect on the purchasing decisions of Isomil Plus Advanced Soya formula milk in Surabaya City.